Optimal Configuration Method of Harmonic Measuring Devices in Distribution Network Based on Power Big Data and Fuzzy Matching Algorithm - Zhang, Yue (2024 International Conference on Artificial Intelligence and Power Systems (AIPS), 2024)
There is a significant difference between the measured values and the actual values of the distribution network harmonic measurement device. It is necessary to design a new optimization configuration method for the distribution network harmonic measurement device based on power big data and fuzzy matching algorithm. Based on big data, the optimization process of generating harmonic detection devices in the distribution network was carried out, and the optimization configuration of harmonic monitoring devices in the distribution network was carried out. The experimental results show that this method has good configuration effect, high measurement accuracy, reliability, and certain application value, making a certain contribution to reducing harmonic detection errors in distribution networks.